Cell surface area and membrane folding in glioblastoma cell lines differing in PTEN and p53 status. - Simon Memmel; Vladimir L Sukhorukov; Marcus Höring; Katherine Westerling; Vanessa Fiedler; Astrid Katzer; Georg Krohne; Michael Flentje; Cholpon S Djuzenova (PLoS ONE, 2014)
Glioblastoma multiforme (GBM) is characterized by rapid growth, invasion and resistance to chemo-/radiotherapy. The complex cell surface morphology with abundant membrane folds, microvilli, filopodia and other membrane extensions is believed to contribute to the highly invasive behavior and therapy resistance of GBM cells. The present study addresses the mechanisms leading to the excessive cell membrane area in five GBM lines differing in mutational status for PTEN and p53. In addition to scanning electron microscopy (SEM), the membrane area and folding were quantified by dielectric measurements of membrane capacitance using the single-cell electrorotation (ROT) technique. The osmotic stability and volume regulation of GBM cells were analyzed by video microscopy. The expression of PTEN, p53, mTOR and several other marker proteins involved in cell growth and membrane synthesis were examined by Western blotting. The combined SEM, ROT and osmotic data provided independent lines of evidence for a large variability in membrane area and folding among tested GBM lines. Thus, DK-MG cells (wild type p53 and wild type PTEN) exhibited the lowest degree of membrane folding, probed by the area-specific capacitance C m = 1.9 µF/cm(2). In contrast, cell lines carrying mutations in both p53 and PTEN (U373-MG and SNB19) showed the highest C m values of 3.7-4.0 µF/cm(2), which corroborate well with their heavily villated cell surface revealed by SEM. Since PTEN and p53 are well-known inhibitors of mTOR, the increased membrane area/folding in mutant GBM lines may be related to the enhanced protein and lipid synthesis due to a deregulation of the mTOR-dependent downstream signaling pathway. Given that membrane folds and extensions are implicated in tumor cell motility and metastasis, the dielectric approach presented here provides a rapid and simple tool for screening the biophysical cell properties in studies on targeting chemo- or radiotherapeutically the migration and invasion of GBM and other tumor types.